Tax Policy and the Asian Crisis - Nellor, David (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1999)
This paper focuses on tax policy and the crisis in Asia in the context of globalization and technological change. Two sets of conclusions, specific tax reform measures and general lessons from the crisis, form the tax policy agenda on these issues. The complexity and volume of financial transactions, associated with the opening of emerging markets, have made tax administration a more challenging task. Just as strengthening financial systems must be a precursor to capital account liberalization, tax administrations clearly also require strengthening in such an environment. In many emerging markets the capacity to tax capital returns is limited. Tax administrators need to understand and monitor complex financial transactions that grew rapidly due both to financial sector liberalization and technological innovation. Traditional difficulties for tax administrators, such as transfer pricing, that had often been limited to natural resource sectors in developing economies, took on wider importance as local companies gained sophistication and developed offshore operations.